Two by two ebook - Sparks, Nicholas (2016)
From a New York Times bestselling author, a single father discovers the true nature of unconditional love after his world his turned upside down. At 32, Russell Green has it all: a stunning wife, a lovable six year-old daughter, a successful career as an advertising executive, and an expansive home in Charlotte. He is living the dream, and his marriage to the bewitching Vivian is at the center of it. But underneath the shiny surface of this perfect existence, fault lines are beginning to appear . . . and no one is more surprised than Russ when every aspect of the life he has taken for granted is turned upside down.    In a matter of months, Russ finds himself without a job or a wife, caring for his young daughter while struggling to adapt to a new and baffling reality. Throwing himself into the wilderness of single parenting, Russ embarks on a journey at once terrifying and rewarding—one that will test his abilities and his emotional resources beyond anything he's ever imagined.    When a chance encounter with an old flame tempts him to take a chance on love again, he will navigate this new opportunity with trepidation and wonder. But with the loyal support of his parents, the wisdom of his older sister, Marge, and the hard-won lessons of fatherhood, Russ will finally come to understand the true nature of unconditional love—that it is a treasure to be bestowed, not earned.